A virtual environment to evaluate the arm volume for lymphedema affected patients. (January 2021) - Vitali, Andrea; Togni, Giovanni; Regazzoni, Daniele; Rizzi, Caterina; Molinero, Guido
Highlights: Arm volume evaluation for lymphedema through 3D scanning and modelling A virtual environment to assess linear and volumetric measurements of an arm with lymphedema Lym 3DLab: a computer-aided tool to automatically compute the measurements of lymphedema Comparison between measurements by Lim 3DLab and by the traditional medical methods A procedure to evaluate the functionalities of Lym 3DLab by involving medical personnel Abstract: Background and Objective: The paper presents a novel procedure based on 3D scanning and 3D modelling to automatically assess linear and volumetric measurements of an arm and to be further applied to patients affected by post breast cancer lymphedema. The aim is the creation of a virtual platform easily usable by medical personnel to get more objective evaluations during the lymphedema treatment. Methods: The procedure is based on the 3D scanning of the arm using the Occipital Structure Sensor and an ad-hoc developed application, named Lym 3DLab. Lym 3DLab emulates the traditional measurement methods, which consist in taking manual circumference measurements or using the water displacement method. These measurements are also used to design the compression stockings, the typical orthopaedic device used for lymphedema treatment. A validation test has been performed to compare the measurements computed by Lym 3DLab with both water displacement and manual circumference measurements. Eight volunteers have been involved who are not affected by lymphedema. Furthermore, a specific usability test has been performed to evaluate the 3D scanning procedure by involving four physiotherapists. Results: The comparison between the volumes has highlighted how all the 3D acquired models have their volumes inside a range of acceptability. This range has been defined by considering the sensitivity error of the tape measure used to measure the water displacement. The comparison between the perimeters of cross sections computed with Lym 3DLab and the circumference measurements has shown results that are very accurate with an average difference of 2 mm. The measure errors have been considered negligible by the medical personnel who have evaluated the proposed procedure more accurate than the traditional ones. The test with physiotherapists has shown a high level of usability of the whole virtual environment, but the 3D scanning procedure requires an appropriate training of the personnel to make the 3D acquisition as fast and efficient as possible. Conclusions: The achieved results and the physiotherapists' feedback allow planning a future test with patients affected by lymphedema in collaboration with the hospital. A further test has been planned to use the computed measurements to design orthopaedic compression stockings.